Measuring the magnetic component of the electromagnetic field - Konstantin G. Dudarev; Igor M. Bondar (Advanced Engineering Research)
A device for measuring the magnetic component of the electromagnetic field is proposed. Magnetodiodes are offered to be used as an electromagnetic field-intensity meter sensing element, and the holometry method - to improve the sensitivity. The proposed meter consists of the standard antenna connected to the calibration generator output, and of the series-connected magnetodiode, filter, processing amplifier, interference-holographic system, and measuring device. The calibration oscillator is made tunable. The application of the discussed above method of measuring the magnetic component of the electromagnetic field will allow significantly improve the accuracy and ease of measurement, will make it possible to create highly sensitive, compact, relatively easy-to-work tools that provide the capability of interfacing with a variety of the output devices and information visualization. In addition, the periodic meter recalibration under the steady-state conditions in the technical center is eliminated. The meter calibration is used for the permanent and timely correction of the changes associated with aging, temperature, pressure, and vibration.